2015
DOI: 10.1007/s10238-015-0381-2
|View full text |Cite
|
Sign up to set email alerts
|

Elevated circulating CD14lowCD16+ monocyte subset in primary biliary cirrhosis correlates with liver injury and promotes Th1 polarization

Abstract: Primary biliary cirrhosis (PBC) is a progressive autoimmune liver disease in which monocytes/macrophages infiltration and skewed T helper type (Th) 1 and Th17 cell responses participate in the development of the disease. Human peripheral blood monocytes are heterogeneous and can be divided into classical CD14CD16, intermediate CD14CD16, and nonclassical CD14CD16 monocyte subsets. Compared to classical monocytes, CD16 monocytes are generally termed pro-inflammatory monocytes and play an important pathogenic rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 35 publications
2
17
0
4
Order By: Relevance
“…Patients with HT were also characterized by an increased frequency of CD86 + non-classical Mo, which has been previously reported in patients with other autoimmune diseases including multiple sclerosis (37), systemic lupus erythematous (38), and primary biliary cirrhosis (39). Variations in sample material, separation protocols, detection methodology and definition of Mo subsets might explain why we did not detect a parallel reduction of classical Mo as observed in other studies (38,39).…”
Section: Discussionsupporting
confidence: 68%
“…Patients with HT were also characterized by an increased frequency of CD86 + non-classical Mo, which has been previously reported in patients with other autoimmune diseases including multiple sclerosis (37), systemic lupus erythematous (38), and primary biliary cirrhosis (39). Variations in sample material, separation protocols, detection methodology and definition of Mo subsets might explain why we did not detect a parallel reduction of classical Mo as observed in other studies (38,39).…”
Section: Discussionsupporting
confidence: 68%
“…Studies have documented that IL-12 is not only able to induce the differentiation of CD4 + naïve T cells into Th1 cells but is also able to drive the polarization of regulatory T cells into Th1-like cells and paralyze their activity by reducing their suppressive capacity [13,14]. [22], and data have demonstrated that in patients with PBC circulating monocytes are increased in frequency and absolute number and are able to produce significantly increased levels of pro-inflammatory cytokines when challenged with different TLR ligands [16,33]. Therefore, the absence of difference in IL-12 production from -24-PBC monocytes that was detected in our in vitro experiments could possibly be explained by the fact that equal numbers of cells were used as with the healthy control samples.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with PBC elevated levels of circulating CD14 low CD16 + monocytes have been reported, and these elevations correlated with increased liver injury and Th1 polarization [16]. Therefore, we studied the ability of monocytes from patients with PBC to produce IL- cytokine have been used across studies, from 10ng/ml to 50ng/ml, to drive the polarization of naïve CD4 + T cells into Th1 cells [19][20][21].…”
Section: P70 Proteinmentioning
confidence: 99%
See 2 more Smart Citations